Pengaruh Penggunaan Media Sparkol Videoscribe Dalam Meningkatkan Keterampilan Menulis Teks Prosedur Siswa Kelas X SMA Pencawan Medan - Sinaga, Devi Ansani Christina; Saragih, Elza Leyli Lisnora; Manurung, Rolan (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study aims to determine the Effect of Using Sparkol Videoscribe Media on Procedural Text Writing Skills in Class X Students of SMA Pencawan Medan in the 2024/2025 Academic Year. This type of research is a quantitative experimental research with a One Group Pre-Test and Post-Test Design research design. The population in this study were 95 class X students of SMA Pencawan Medan in the 2024/2025 Academic Year who were distributed into 3 classes determined by the cluster sampling technique. The data analysis technique used was the normality test using the F test, the homogeneity test and the hypothesis test. In accordance with this quantitative method which seeks to present data in an ongoing study, the calculation of the hypothesis in this study was tested using the "t" test at a significance level of a = 0.05. From the calculation data, tcount> ttable = 2.60> 1.86, therefore, the null hypothesis (H₂) is rejected and the alternative hypothesis (H₂) is accepted. Thus, it can be concluded that there is an Influence of the Use of Sparkol Videoscribe Media in Improving the Writing Skills of Procedural Texts of Class X Students of SMA Pencawan Medan in the 2024/2025 Academic Year.